As concepções de professor e suas influências para a formação docente em Educação Física - Anes, Rodrigo Roncato Marques (2013)
This work is linked to the research line formation, Teacher Professionalization and educational practices and is inserted as part of the work developed by Redecentro - Network of researchers on teachers (as) in the Midwest. The work was guided by historical materialism dialectical method, addressed the issue of teacher design and aimed investigates the conceptions of teacher submitted and published in academic productions in Education (theses and dissertations) that deal with the physical education teacher, produced the period 1999-2007, to understand whether and which produce meanings for teaching social function in that area. It is a state of knowledge about the academic production on the teacher's Midwest Region. The specific objectives were to understand the pedagogical ideals and how they appear in productions in Education; analyze the current context of teacher education and physical education teachers in Brazil, and the political and ideological directions for teaching social function; investigate in the database Redecentro, yields on the Physical Education teacher and analyze the conceptions of teacher submitted by them; understand, through the analysis of the data collected and selected, the meanings attributed to the social role of the teacher and its effects on area of Physical Education. The research is characterized as bibliographic and structured through a qualitative approach. The theoretical construction was supported by authors based critical area of Education and Physical Education, to understand the teacher and their conceptions, in history and in contemporary The selection process of the empirical data came from 492 papers defended between 1999 and 2007 and analyzed by Redecentro in their first three phases of research. That number from the cut set, we got eight productions that focus on the physical education teacher. Analysis of the information collected had as its starting point the general understanding of the productions (as structured, organized and are based) and then, from the categories of analysis Pedagogical ideas (Design Professor and Lecturer Social Function) and Teaching Work, sought to highlight the concepts raised by research and meanings that have the social function of the physical education teacher. The research has enabled us to understand that the concept of teacher most obvious is related to a critical perspective and guided by ideals historical materialist dialectic, however, such a conception is only well defended and explained by those jobs that can best demonstrate the joint theoretical-methodological and a clear epistemological membership, especially the dialectical-materialist method. It was evident that the absence of the method in some research undertakes the presentation of their theoretical perspectives, undermines explain their political positions and his speeches about the teaching profession, and as a consequence, not just theoretically sustaining a conception of critical physical